Significance of Hematological Parameters in Uncomplicated Diabetes Mellitus - Neha Bhatt1 , Pratibha Dawande2 , Obaid Noman3 , Sweta Bahadure3 , Arvind Bhake4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Diabetes mellitus leads in chronic metabolic syndromes worldwide. The physiochemicalchanges in the blood bought about by persistent hyperglycemia are reflected in the hematological parameterson complete blood count.Introduction: Diabetes Mellitus is a smouldering global pandemic destroying mankind slowly and silently.The associated detainable microvascular and macrovascular complications are responsible for much ofmorbidity and mortality. With ever increasing incidence and prevalence, it is important to device economicalmethod to easily monitor, predict and prevent untoward health outcomes in these patients. Complete bloodcount being used as a basic and easily available investigation can be utilized for this purpose.Material and Method: A case control study was carried out at Datta Meghe Medical College and ShaliniTai Meghe Hospital and research center in association with Acharya Vinobha Bhave hospital & researchcenter and Jawaharlal Medical College, both a tertiary care hospital for a duration of 3 months. Study groupof 100 diabetic patients and control group of 100 nondiabetic patients were evaluated using questionnaire,clinical findings, case records and hematological findings. Hemogram was analysed on Beckman coulter fivepart cell counter. Leishman stained peripheral smears were studied. The data thus collected was analysedusing test of significance to find out relevance of changes in hematological parameters in diabetic patients.Results: Anaemia along with higher leucocyte and platelet counts were observed in diabetic group.Conclusion: Monitoring changes in hematological parameters can be a useful tool in better management ofdiabetic patients.